Empowering Sudanese Women and Promoting Their Health and Well-Being. Issue 5 (September 2015) - Callister, Lynn Clark
<x xml:space="preserve">Abstract</x> Individual efforts of courageous women in under-resourced countries are making a difference to move forward in achieving the Millennium Development Goals.